Landscape architectural perspectives as an agent for generous design - Inge Bobbink; Saskia de Wit (Research in Urbanism Series, 2020)
Landscape architectonic compositions that draw on the underlying landscape structure can function as a carrier for changing programmes, cultures, processes, etc. Precisely such an explicitly spatial design is required to foster the inclusive city, one that is not only socially just but also sensitive to the environment while allowing for and evoking diverse social and natural processes. The objective of an ‘inclusive city’ is  often related to social issues, which might easily lead to the exclusion of ecological values; the opposite approach may prove equally exclusive. Inclusivity also means creating room for the unexpected. From a design point of view, this requires two underlying attitudes: a willingness to see any design assignment from different perspectives as well as a readiness to create sustainable, flexible and open designs.